Advances in interpretation of subsurface processes with time‐lapse electrical imaging. Issue 6 (8th August 2014) - Singha, K.; Day‐Lewis, F. D.; Johnson, T.; Slater, L. D.
Abstract Electrical geophysical methods, including electrical resistivity, time‐domain induced polarization, and complex resistivity, have become commonly used to image the near subsurface. Here, we outline their utility for time‐lapse imaging of hydrological, geochemical, and biogeochemical processes, focusing on new instrumentation, processing, and analysis techniques specific to monitoring. We review data collection procedures, parameters measured, and petrophysical relationships and then outline the state of the science with respect to inversion methodologies, including coupled inversion. We conclude by highlighting recent research focused on innovative applications of time‐lapse imaging in hydrology, biology, ecology, and geochemistry, among other areas of interest. Copyright © 2014 John Wiley & Sons, Ltd.